Ethnic disparities in the association between low-grade inflammation biomarkers and chronic kidney disease: The HELIUS Cohort Study - Mosterd, C.M.; Hayfron-Benjamin, C.F.; van den Born, B-J.H.; Maitland - van der Zee, A.H.; Agyemang, C.; van Raalte, D.H. (Journal of Diabetes and Its Complications, 2022)
Aims: Ethnic differences exist in the prevalence and progression of chronic kidney disease (CKD). However, underlying mechanisms remain unclear. It has been proposed that chronic low-grade inflammation plays an important role in CKD pathogenesis. In the current analysis, we study the association between systemic inflammatory biomarkers and CKD prevalence in different ethnic groups. Methods: We examined cross-sectional associations between biomarkers of low-grade inflammation, including serum high-sensitive (hs)-CRP, fibrinogen, and D-dimer, and CKD prevalence in different ethnic groups residing in Amsterdam, the Netherlands. We included 5740 participants (similar-sized Dutch, African Surinamese, South Asian Surinamese, Ghanaian, Turkish and Moroccan populations) aged 18 to 70 years of the Healthy Life in an Urban Setting study (HELIUS) cohort. Results: In the fully adjusted models, adjusted for ethnicity-specific cut-off values, elevated fibrinogen [odds ratio 2.50 (95 % confidence interval 1.10–5.78)] and D-dimer [2.99 (1.28–7.00)] were significantly associated with CKD in Dutch. In South-Asian Surinamese, a significant association with elevated D-dimer [2.66 (1.32–5.37)] was found. Conclusions: Our study shows that there are both differences in biomarker levels and the association with CKD across ethnic groups. Future research to identify potential drivers of the differential associations and susceptibility of CKD among ethnic groups to reduce the CKD burden is necessary.
Research Article
Keywords: Ethnicity; Inflammatory biomarkers; Chronic kidney disease; D-dimer; Fibrinogen; C-reactive protein